B is for bulldozer : a construction ABC - Sobel, June.; Iwai, Melissa (San Diego : Harcourt, 2003)
As children watch over the course of a year, builders construct a rollercoaster using tools and materials that begin with each letter of the alphabet.
Keywords: Roller coasters -- Fiction; Building -- Fiction; Construction equipment -- Fiction; Alphabet; Stories in rhyme